2009
DOI: 10.1007/s10453-009-9121-y
|View full text |Cite
|
Sign up to set email alerts
|

Possible cause of allergy for the librarians: books manipulation and ventilation as sources of fungus spores spreading

Abstract: The objective of this study was to investigate the airborne viable spore concentrations and identify the fungal species in all indoor spaces from the lending library at the Technical University ''Gheorghe Asachi'' Iaşi, Romania. Samples were collected using the settle plate method and swab samples from PC cooler fan grids as well as from the wall in it's vicinity and from paper/wood fragments. There were no air conditioning systems in the library rooms. The heating systems were standard with an environmental t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…It has been demonstrated that the presence of C. globosum in the indoor environment is one of the important contributors to the development of symptoms of rhinitis, asthma and other health problems (Vesper et al., 2007, Apetrei et al., 2009, Polizzi et al., 2009, Mason et al., 2010, Miller and McMullin, 2014). This species is also the most common human pathogen mainly associated with onychomycosis (Naidu et al., 1991, Stiller et al., 1992, Aspiroz et al., 2007, Latha et al., 2010, Tullio et al., 2010, Hwang et al., 2012, Lagacé and Cellier, 2012, Kim et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the presence of C. globosum in the indoor environment is one of the important contributors to the development of symptoms of rhinitis, asthma and other health problems (Vesper et al., 2007, Apetrei et al., 2009, Polizzi et al., 2009, Mason et al., 2010, Miller and McMullin, 2014). This species is also the most common human pathogen mainly associated with onychomycosis (Naidu et al., 1991, Stiller et al., 1992, Aspiroz et al., 2007, Latha et al., 2010, Tullio et al., 2010, Hwang et al., 2012, Lagacé and Cellier, 2012, Kim et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these species have been reported to be important inhalant allergens. They contribute to the development of the symptoms of both rhinitis and asthma due to the production of mycotoxins and microbial volatile organic compounds as well as the liberation of ascospores and hyphal fragments in the indoor environment (Gonianakis et al., 2005, Apetrei et al., 2009, Polizzi et al., 2009, Mason et al., 2010, Andersen et al., 2011, Miller and McMullin, 2014). Chaetomium globosum is the most common species of the Chaetomiaceae in the indoor environment (Vesper et al., 2007, Ayanbimpe et al., 2010, Straus, 2011, McMullin et al., 2013, Miller and McMullin, 2014), and this species can already be present in new gypsum wallboard (Andersen et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, these fungal spores can easily penetrate indoor environments by means of ventilation systems and human transport. Once indoors, the spores readily germinate, form colonies and, during these processes, decompose the organic matter of the paper collections (Apetrei et al 2009). By contrast, bacteria rarely exist on paper and their number increases significantly only when the library collections become damp or flooded.…”
Section: Introductionmentioning
confidence: 99%
“…spores, viruses (and all their fragments and byproducts) represent a hazard both for the heritage materials, which can become deteriorated, and for operators and visitors (Apetrei et al 2009;Caneva et al 2007;Gallo 1993;Mandrioli and Ariatti 2001;Mandrioli et al 2003;Mandrioli 2006;Niesler et al 2010;Pasquariello 2006;Pasquariello et al 2008;Tarsitani et al 1996;Tarsitani 2007).…”
mentioning
confidence: 96%
“…Depending on their size, particles settle on surfaces at different rates, and if they find favourable nutritional and environmental conditions, they may cause biodegradation of heritage materials, which in turn generates economic and cultural losses. Allergenic particles that are either inhaled or come into contact with the skin can give rise to serious problems in humans (Apetrei et al 2009;Wiszniewska et al 2009). …”
mentioning
confidence: 99%